The Effect of Bank Liquidity Creation and Bank Funding Diversity on Non-Performing Loan with Bank Size as Moderating Variable - Sativa Putri Adenanny; Muhammad Amin Kadafi; Herry Ramadhani; Margareth Henrika (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Bank Liquidity Creation (BLC) and Bank Funding Diversity (BFD) on Non-Performing Loans (NPLs), as well as the moderating role of Bank Size in strengthening or weakening these relationships. The research uses a quantitative approach with secondary data obtained from the financial statements of national private commercial banks in Indonesia for the 2022–2024 period. The sample was selected using a purposive sampling method, resulting in 58 banking units observed over three years. The dependent variable in this study is Non-Performing Loans, while the independent variables consist of Bank Liquidity Creation and Bank Funding Diversity, with Bank Size serving as the moderating variable. Data were analyzed using panel data regression with the assistance of EViews 12 and the Random Effect Model (REM) was identified as the most appropriate model. The results show that Bank Liquidity Creation has a positive but insignificant effect on NPLs, while Bank Funding Diversity has a negative and significant effect on NPLs. Bank Size is found to have a positive but insignificant direct effect on NPLs. Bank Size does not significantly moderate the relationship between Liquidity Creation and NPLs, but it significantly strengthens the negative effect of Funding Diversity on NPLs. These findings highlight the importance of diversified funding structures and effective risk management practices in reducing credit risk within the Indonesian banking sector